Comi, Gostei e Postei: Tripadvisor e Experiências Marcantes em Restaurantes / I Ate, I Enjoyed and I Posted: Tripadvisor and Marvelous Experiences in Restaurants - Cechinel, Eduardo; Santos, Aline Regina (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2018)
Este artigo objetivou, por meio de abordagem qualitativa, identificar o cenário de serviços e as interações humanas, em comentários feitos por clientes de restaurantes no site TripAdvisor. Incialmente realizou-se uma revisão teórica sobre os temas experiência do cliente; boca-a-boca eletrônico; cenário de serviços e interações humanas, para situá-los nos critérios de investigação. A seguir foram analisados 1.350 depoimentos publicados no TripAdvisor, por clientes de restaurante que tenham classificado suas experiências nos mesmos como excelente. Os resultados permitem compreender o impacto que o cenário de serviços e as interações humanas têm na composição do relato das experiências vivenciadas por frequentadores de restaurantes. PALAVRAS-CHAVE Turismo. Restaurantes. Experiência em Serviços. Boca-a-Boca Eletrônico. TripAdvisor. ABSTRACT The article aimed, through a qualitative approach, to identify influence of the servicescape and the human interactions in the comments by restaurant customers on the TripAdvisor website. A theoretical review was carried out on the themes customer’s experience; electronic words of mouth; servicescape and human interactions, to place them in the research criteria. We have analyzed 1350 testimonials published on TripAdvisor by restaurant customers who rated their experiences in them as excellent. The results allow us to understand the impact that the servicescape and human interactions have on the composition of the experiences reported by customers who attend restaurants. KEYWORDS Tourism. Restaurant. Service Experience. Word of Mouth. TripAdvisor. AUTORES Eduardo Cechinel - Mestrando em Administração, Universidade do Estado de Santa Catarina, Florianópolis, Santa Catarina, Brasil. Currículo: http://lattes.cnpq.br/6364280886168071. E-mail: educechinel@hotmail.com Aline Regina Santos – Doutora. Professora no Mestrado Acadêmico e no Departamento de Administração Pública, Universidade do Estado de Santa Catarina, Florianópolis, Santa Catarina, Brasil. Currículo: http://lattes.cnpq.br/9210124458700096 E-mail: aline_san@yahoo.com.br REFERENCIAS Associação Brasileira de Bares e Restaurante. (2016). Perfil da Abrasel. Link Anderson, E. W. (1998). Customer satisfaction and word of mouth. Journal of Service Research, 1(1), 5-17. Link Andersson, T. D. & Mossberg, L. (2004). The dining experience: do restaurants satisfy customer needs? Food Service Technology, 4, 171-177. Link Barbosa, M. L. A. & Farias, S. A. (2012). Em busca de uma experiência extraordinária em serviços de restaurante. Revista Rosa dos Ventos Turismo e Hospitalidade, 4(3), 440-454. Link Basso, K., Reck & D.,Rech, E. (2013). Personalidade e boca a boca: propensão ao envio e recebimento de informações. Revista Administração de Empresas, 53(6), 580-591. Link Bateson, J. E. G. & Hoffman, K. D. (2001). Marketing de Serviços. Porto Alegre: Bookman. Bettencourt, L. & Gwinner, K. (1996).Customization of the service experience: the role of the frontline employee. International Journal of Service Industry Management, 7(2). Link Bharwani, S. & Mathews, D. (2016) Customer service innovations in the Indian hospitality industry. Worldwide Hospitality and Tourism Themes, 8(4), 416-431. Link Bitner, M. J. (1990). Evaluating services encounters: the effects of physical surroundings and employee’s responses. Journal of Marketing, 54(2), 69-82. Link Bitner, M. J. (1992). Servicescapes: The impact of physical surroundings on customers and employees. Journal of marketing, 56(2), 57-71. Link Bolton et al.. (2014). Small details that make big differences: A radical approach to consumption experience as a firm’s differentiating strategy. Journal of Service Management, 25(2), 253-274. Link Bone, P. F. (1995). Word-of-mouth effects on short-term and long-term product judgments. Journal of Business Research, 32(3), 213–223. Link Creswell, J. W. (2010) Projeto de pesquisa: métodos qualitativo, quantitativo e misto. Porto Alegre: Artmed. Dong, P. & Siu, N. Y. (2012) Servicescape elements, customer predispositions and service experience: The case of theme park visitors. Tourism Management, 36(3), 541-551. Link Flick, U. (2004) Uma introdução à pesquisa qualitativa. Porto Alegre: Bookman. Fu, X. Z., Tanyatanaboon, M. & Lehto, X. Y. (2015) Conceptualizing transformative guest experience at retreat centers. International Journal of Hospitality Management, 49(3), 83-92. Link Gibbs, G. (2009) Análise de dados qualitativos. Porto Alegre: Artmed. Gimenes, M. H. S. G., Brea, J. A. F & Gândara, J. M. (2012). Comidas Inovidables: La construcción de uma metodologia para analizar las experiencie de comer fuera de casa. Estudios y Perspectivas en Turismo, 21(4), 802-824. Link Grönroos, C. (2009). Marketing: gerenciamento e serviços. Rio de Janeiro: Elsevier. Gustafsson, I. B., Ostrom, A., Johansson, J., Mossberg, L. (2006). The five aspects meal model: a tool for developing meal services in restaurants. Journal of Foodservice, 17(2), 84-93. Link Hanefors, M. & Mossberg, L. (2003). searching for the extraordinary meal experience. Journal of Business & Management, 9(3), 249-270. <a href="http://web.b.ebscohost.com/abstract?direct=true&profile=ehost&scope=site&authtype=crawler&jrnl=1535668X&AN=12866604&h=%2bJXQowE%2fFRpQGkDJXjBeMCF59I2ZtnOEewfMrqamjSvYfTZvVdUOWouBXGt4dX%2bktPw5LvgRDWJQ6YpMg45vFw%3d%3d&crl=f&resultNs=AdminWebAuth&resultLocal=ErrCrlNotAuth&crlhashurl=login.aspx%3fdirect%3dtrue%26profile%3dehost%26scope%3dsite%26authtype%3dcrawler%26jrnl%3d1535668X%26AN%3d12866604">Link Hennig-Thurau, T., Gwinner, K. P., Walsh, G. e Gremler, D. D. (2004). Electronic word-of-mouth via consumer-opinion platforms: What motivates consumers to articulate themselves on the Internet?. Journal of Interactive Marketing, 18(1), 38-52. Link Klaus, P. & Maklan, S. (2012). EXQ: a multiple-item scale for assessing service experience. Journal of Service Management, 23(1), 5-33. Link Kucukemiroglu, S. Kara, A. (2015). Online word-of-mouth communication on social networking. International Journal of Commerce and Management, 25(1), 2-20. Link Lang, B. (2011). How word of mouth communication varies across service encounters. Managing Service Quality: An International Journal, 21(6), 583-598. Link Longart, P. (2010). What drives word-of-mouth in restaurants? International Journal of Contemporary Hospitality Management. 22(1), 121-128. Link Lovelock, C. H. (1994). Product plus: How product b + s service = competitive advantage. New York, NY: McGraw-Hill Lovelock, C H & Wright, L. (2003) Serviços: marketing e gestão. São Paulo: Saraiva. Oliver, R. L., Rust, R. T. & Varki, S. (1997). Customer delight: foundations, findings, and managerial insight. Journal of Retailing, 73(3), 311-336. Link Pai, M., Chu, H., Wang, S., Chen, Y. (2013). Electronic word of mouth analysis for service experience. Expert Systems with Applications, 40(6), 1993-2006. Link Palmer, A. (2010). Customer experience management: a critical review of an emerging idea. Journal of Services Marketing, 24(3), 196-208. Link Pareigis, J. Echeverri, P. & Edvardsson, B. (2012). Exploring internal mechanisms forming customer servicescape experiences. Journal of Service Management, 23(5), 677-695. Link Perussi, R. F. & Teles, R. M. S. (2010). Ensaio metodológico para a prospecção mercadológica para empreendimentos gastronômicos. Revista Turismo em Análise, 21 (2), 341-356. Link Pine II, B. J. & Gilmore, J. H. (1998). Welcome to the experience economy. Harvard Business Review, 76(4), 97-105. Link Pine II, B. J. & Gilmore, J. H. (2014). A leader's guide to innovation in the experience economy. Strategy & Leadership, 42(1), 24-29. Link Rageh, A., Melewar, T. C. & Woodside, A. (2013) Using netnography research method to reveal the underlying dimensions of the customer/tourist experience. Qualitative Market Research: An International Journal, 16(2), 126-149. Link Reimer, A. & Kuehn, R. (2004). The impact of servicescape on quality perception. European Journal of Marketing, 39(7/8), 785-808. Link Saunders, M., Lewis, P., & Thornhill, A. (2007). Research Methods for Business Students, (6 ed.). London: Pearson. Schmitt, B. H. (1999). Experiential marketing. New York, NY: Free Press. Sebrae - Serviço Brasileiro de Apoio às Micro e Pequenas Empresas. (2016) Bares e restaurantes: um setor em expansão. Link Serra, D. E. S. & Soto-Sanfiel, M. T. (2014). Quando o usuário se torna um publicitário: motivações para ewom - propaganda boca a boca eletrônica - no Facebook. REMark – Revista Brasileira de Marketing, 13(1), 1-16. Link Sundaram, D. S. & Webster, C. (2000). The role of nonverbal communication in service encounters. Journal of Services Marketing, 14(5), 378-391. Link Tomas, R. N., Meschgrahw, R. P. & Alcantara, R. L. C. (2012). Social networking and consumer buying behavior: is the reign of ‘word-of-mouth’ back? REMark – Revista Brasileira de Marketing, 11(2), 120-147. Link Tripadvisor (2016) (Org.). Mudanças no algoritmo do ranking de popularidade do TripAdvisor. 2016. Link Tubenchlak, D. B., Faveri, D., Zanini, M. T. & Goldszmidt, R. (2015). Motivações da comunicação boca a boca eletrônica positiva entre consumidores no Facebook. Revista de Administração Contemporânea, 19(1), 107-126. Link Vasconcelos, A. M., Barichello, R., Lezana, A., Forcellini, F. A., Ferreira, M. G. G. & Miguel, P. A. C (2015). Conceptualisation of the service experience by means of a literature review. Benchmarking: An International Journal, 22(7), 1301-1314. Link Verhoef, P. C., Lemon, K. N., Parasuraman, A., Roggeveen, A., Tsiros, M. & Schlesinger, L. A. (2009). Customer experience creation: determinants, dynamics and management strategies. Journal of Retailing, 85(1), 31-41. Link Walter, U. & Edvardsson, B. (2012). The physical environment as a driver of customers' service experiences at restaurants. International Journal of Quality and Service Sciences, 4(2), 104-119. Link Weber, A. J., King, S. C. & Meiselman, H. L. (2004). Effects of social interaction, physical environment and food choice freedom on consumption in a meal-testing environment. Appetite, 42(1), 115–118. Link Zeithaml, V. A., Bitner, M. J. & Gremler, D. (2014). Marketing de serviços: a empresa com foco no cliente. Porto Alegre: Bookman. PROCESSO EDITORIAL Recebido: 07 ABR 2017; Avaliado: MAI – JUN 2017; Avaliado 2: AGO – SET; Aceito: 05 JAN 2018